Patient, carer and healthcare professional perspectives on increasing calorie intake in Amyotrophic Lateral Sclerosis. (June 2023) - Coates, Elizabeth; Zarotti, Nicolò; Williams, Isobel; White, Sean; Halliday, Vanessa; Beever, Daniel; Hackney, Gemma; Stavroulakis, Theocharis; White, David; Norman, Paul; McDermott, Christopher; ,
Objectives: Research suggests that higher Body Mass Index is associated with improved survival in people with Amyotrophic Lateral Sclerosis (pwALS). Yet, understanding of the barriers and enablers to increasing calorie intake is limited. This study sought to explore these issues from the perspective of pwALS, informal carers, and healthcare professionals. Methods: Interviews with 18 pwALS and 16 informal carers, and focus groups with 51 healthcare professionals. Data were analysed using template analysis and mapped to the COM-B model and Theoretical Domains Framework (TDF). Results: All three COM-B components (Capability, Opportunity and Motivation) are important to achieving high calorie diets in pwALS. Eleven TDF domains were identified: Physical skills (ALS symptoms); Knowledge (about high calorie diets and healthy eating); Memory, attention, and decision processes (reflecting cognitive difficulties); Environmental context/resources (availability of informal and formal carers); Social influences (social aspects of eating); Beliefs about consequences (healthy eating vs. high calorie diets); Identity (interest in health lifestyles); Goals (sense of control); Reinforcement (eating habits); and Optimism and Emotion (low mood, poor appetite). Discussion: To promote high calorie diets for pwALS, greater clarity around the rationale and content of recommended diets is needed. Interventions should be tailored to patient symptoms, preferences, motivations, and opportunities.